2016
DOI: 10.1155/2016/7965689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wound Healing Properties of Grape Seed, Sesame, and Fenugreek Oils

Abstract: Background. Medicinal plants have proved at all times to be a powerful remedy for health care. Accordingly, grape seed, sesame, and fenugreek extracted oils with pharmacological properties are investigated as wound treatments. This study assesses the potential of our oils for healing wounds induced on rats. Methods. Phytochemical analyses of oils have involved: quality value, polyphenol, chlorophylls, carotene, and fatty acids. Antibacterial activity was carried out. Antioxidant activity was evaluated: the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Its dried seeds contain from 10% to 16% grape oil (Fontanel, ; Janeš & Kočevar Glavač, ). In cold pressed grape oil, linoleic acid (polyunsaturated fatty acid) is the most abundant fatty acid in triglycerides, with a content ranging from 66% to 75%, followed by oleic (20%), palmitic (7%), and stearic (4%) acids (Garavaglia, Markoski, Oliveira, & Marcadenti, ; Janeš & Kočevar Glavač, ; Moalla Rekik et al, ).…”
Section: Polyunsaturated Fatty Acid‐based Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its dried seeds contain from 10% to 16% grape oil (Fontanel, ; Janeš & Kočevar Glavač, ). In cold pressed grape oil, linoleic acid (polyunsaturated fatty acid) is the most abundant fatty acid in triglycerides, with a content ranging from 66% to 75%, followed by oleic (20%), palmitic (7%), and stearic (4%) acids (Garavaglia, Markoski, Oliveira, & Marcadenti, ; Janeš & Kočevar Glavač, ; Moalla Rekik et al, ).…”
Section: Polyunsaturated Fatty Acid‐based Oilsmentioning
confidence: 99%
“…A study using an excision wound model on rats showed the efficacy of grape oil to reduce wound size, increase the content of hydroxyproline in the granulation tissue, and promote the formation of a dense matrix of collagen fibres. Triglycerides or the respective fatty acids, as well as polyphenol compounds (191mg/kg; Moalla Rekik et al, ), may be responsible for wound healing. The results were significant compared with control groups (petrolatum and antibiotic mupirocin).…”
Section: Polyunsaturated Fatty Acid‐based Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that shea butter was a famous antioxidant and anti-inflammatory plant seed extract used in the cosmetic industry because of its high percentage of unsaponifiable compounds including tocopherols and phytosterols [13,14]. Rekik et al also reported that the positive effect of vitamin E and phytosterols on collagen synthesis and skin wound healing is because these compounds prevent the damaging effects of free radicals and ensure the stability and integrity of biological membranes [15]. With increasing interest in the development of functional materials with very few side effects, studies are being conducted to find various plant extracts that inhibit skin aging.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main constituents of fenugreek oil are extremely useful in reducing free radicals 60 . It has been found that fenugreek seed oil is good source of nutraceticals like; α-tocopherol, ALA and sterols 62 as well as also a rich source of vitamin A 64 . Due to the presence of phytoconstituents fenugreek oil proved to have better activity on wound healing 64 and it is found best and safest treatment for male infertility 61 .…”
mentioning
confidence: 99%